PENGARUH RASIO LEVERAGE DAN FIRM SIZE TERHADAP KINERJA KEUANGAN PERUSAHAAN (STUDI PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BEI PERIODE TAHUN 2015 SAMPAI 2018) - Putri, Farisa Oktiviani; Makhdalena, Makhdalena; R M Riadi, R M Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstrack: This study aims to see the effect of leverage and firm size on financial performance both simultaneously and partially in the Food and Beverage Sub-Sector Companies listed on the Indonesia Stock Exchange for the period 2015 to 2018. The population of this study is all companies in the food and beverage sub-sector. listed on the Indonesia Stock Exchange from 2015 to 2018, which has data on ROA, Leverage and Firm Size. Total 16 companies. This study uses secondary data sourced from the Indonesian Capital Market Directory (ICMD). The data analysis technique used is path analysis with the help of the SPSS (Statistical Package for Social Science) program. The results show that the leverage and firm size simultaneously affect the company's financial performance. Leverage partially has a negative effect on the company's financial performance. Meanwhile, firm size has a positive effect on the company's financial performance.Key Words: Leverage, Firm Size, Company’s Financial Performance